THE OPERATIONAL READINESS FOR ANTI SUBMARINE INDONESIAN NAVAL BY USING ANTI SUBMARINE HELICOPTER - Muksin Muksin; Udisubakti Ciptomulyono; Sutrisno Sutrisno; Sunarta Sunarta (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
Some of the Indonesian naval effort to see and protect the Indonesian territory is by using Helicopter sea patrol. In the other side, submarines are the most strategic weapons in the world that can provide a deterrence effect which has a very significant impact on the maritime powers of the countries operating them in the era of generation 4.0 war. Operational readiness is very important, there are readiness in building operational readiness for naval defense through budget fulfillment, utilization of existing resources, procurement and naval modernization by paying attention to Life Cycle Cost, and interoperability while still paying attention to paradigm shifts in naval capability. So, the combat readiness is the condition of the Indonesian Navy's defense equipment and its constituent units, resources and personnel, weapon systems and other military technology equipment in a condition that is ready to carry out military operations in an unspecified time, or function consistent with the purpose for which the defense equipment is organized or designed, the management of resources and training personnel in preparation for combat in the face of the threat of modern warfare in a state of constant combat readiness. At this time, training in Anti-Submarine Warfare conducted by Indonesian Navy’s Helicopter is still limited to carrying out flight procedures, communication procedures with the KRI and the command line, because Helicopters have sensors, weapons and command that need to be upgraded and The personnel also have underwater warfare capabilities that need to be upgraded, so there needs to be an increase in the capability of the helicopter and human resources. Technometry will be used to calculate the Heli's current readiness level. Keywords: Submarine, Anti Submarine Helicopter and operational readiness